Intraocular Cytokine Levels in Post-Cataract Endophthalmitis and their Association with Visual Outcome. (18th August 2018) - Sauer, Arnaud; Candolfi, Ermanno; Gaucher, David; Creuzot-Garcher, Catherine; Bron, Alain; Chiquet, Christophe; Berrod, Jean-Paul; Meyer, Nicolas; Prevost, Gilles; Bourcier, Tristan
ABSTRACT: Purpose : The host immune reaction during endophthalmitis, studied in particular through the intraocular cytokine network, is essential for the comprehension of the disease and the development of new therapies. Therefore, the purpose of this study was to elucidate the cytokine composition of aqueous humor during endophthalmitis. Methods : In a multicenter case-control study, forty-nine patients with postoperative endophthalmitis and 60 controls (cataract surgery) were included. Visual acuity, local inflammatory grading, medical history and intraocular levels of 27 cytokines and chemokines (measured by multiplex immunoassay) were recorded. Results : During endophtalmitis, an increase in total cytokines was observed. The raise of Th1 cytokines was particularly noticeable. Chemokines, such as IL-8, MIP-1 β, MCP-1, G-CSF and IP-10, also increased. Pearson's correlation analyses showed a poor visual prognosis with high levels of IL-8, MCP-1 and VEGF and a low level of IL-10 at admission. Conclusion : An increase in inflammatory cytokines is noticeable during endophthalmitis, with a particular emphasis on IL-8, MCP-1 and VEGF. Targeted anti-inflammatory and anti-VEGF treatments may be of interest in the future.